The Effect of the Holding Time on the Formation of Niobium-Vanadium Carbide Coating Onto Aisi 420 by Thermo Reactive Diffusion Process - Husen Haekal; Fahmi Mubarok (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2020)
The deep drawing process had been widely used in automobile, aerospace, electronics, and allied industries to produce hollow parts. The quality of the deep drawing is determined by the dies properties especially their wear-resistant and hardness. Austenitic stainless steel AISI 420 is one of the material of choice for making these dies. In order to increase the wear resistance of the dies, surface treatment such as thermo-reactive diffusion (TRD) technique can be applied owing to their simplicity, low cost, and environment friendly process. TRD technique able to deposit hard layers of carbide, nitride, or carbonitride In this research, TRD techniques will be employed to AISI 420 with special attention given to the effect of holding time during TRD process to form niobium-vanadium carbide (NbVC) coating. The TRD process is carried out by the powder-pack method in a sealed steel container containing powder mixture of niobium and vanadium as master alloy, alumina (Al2O3) as an inert filler and ammonium chloride (NH4Cl) as an activator. The samples were covered with powder mixture and then heated in the electric resistance furnace for 2, 4, and 6 hours at 1000˚C. The crosssection analysis of the NbVC coating observed under microscopy shows that coating thickness increased with longer holding time with 6.95 µm measured in 6 hours holding time. The high hardness of 1333.2 HV also found in the longest holding time of 6 hours. This high hardness is expected to contribute in the wear resistance characterisitic of AISI 420 dies.